Two-stage surgery for intraperitoneal and retroperitoneal multicentric liposarcoma causing hydronephrosis: a case report - Ryohei Murata; Tadashi Yoshida; Nobuhiro Kobayashi; Yoshito Watanabe; Shigenori Homma; Hayato Echizenya; Akinobu Taketomi (Surgical Case Reports)
Abstract Background Liposarcoma is a soft tissue sarcoma of adipocyte origin. Liposarcoma represents 20–30% of adult soft tissue tumors, which was most frequently seen in the retroperitoneal space in 45% and abdominal space in only 5% of cases, but the multicentric case is unknown. Herein, we describe a rare case of multicentric, large, intra-abdominal and retroperitoneal liposarcoma, one of which had caused infection and pressing the right ureter causing hydronephrosis, which was resected by two-stage surgery. Case presentation The patient was a 46-year-old man who was referred for abdominal bloating and fatigue. Enhanced computed tomography showed a 23-cm intra-abdominal tumor and a 14.6-cm left retroperitoneal tumor. The intra-abdominal tumor which compressed the right ureter caused right unilateral hydronephrosis and deteriorated the renal function. The intra-abdominal tumor had also formed an intra-abdominal abscess. We performed emergent laparotomy and resected the intra-abdominal tumor. After the recovery of renal function, we resected the residual retroperitoneal tumor. Histopathological examination showed both tumors to be myxoid/round cell type liposarcoma. Considering clinical findings and their location, he was diagnosed with multicentric liposarcoma. He underwent adjuvant chemotherapy and has been alive without any recurrence for 9 months after the operation. Conclusions We successfully resected large intra-abdominal and retroperitoneal multicentric myxoid/round cell liposarcomas. A two-stage surgery was a rational choice as it provides time to confirm the recovery of renal function.